SOURCE ROCK EVALUATION WITH INTERPRETATION OF WIRELINE LOGS: A CASE STUDY OF LOWER INDUS BASIN, PAKISTAN - Aadil, N.; Tayyab, M. H.; Naji, A. M. (The Nucleus, 2014)
The qualitative interpretation of the log data succeeds in translating the inherited log responses into organic content and source rock identification. The quantitative interpretation of the petrophysical parameters helped in determination of the total organic content and source rock potential. The criteria for distinguishing shale from sedimentary layers are low density, high sonic transit time, high porosity and high resistivity of shales. The responses of wireline logs in relation to the increasing of organic matter (OM) content is detected through crossplot technique. By this way, the organic matter is identified with increasing in gamma-ray values, sonic transit-time, neutron porosity, resistivity and with reduction in the formation bulk density. The open hole well log data (DLL, FDC, BHC and CNL) of SANN-1 well of Kirthar Trough, Southern Indus Basin (Sindh province) Pakistan, is utilized to determine the organic content of Lower Goru and Sember formations. In this paper, an attempt was made to establish a quantity correlation between standard well logs (sonic, density, neutron and resistivity) and total organic carbon by means of a technique called Î”LogR. In calculating total organic carbon content (TOC), porosity/resistivity overlay technique was used. TOC measured by Î” logR technique at depth interval between 3270 to 3585 meters yielded an average value of 2.78% for Lower Goru Formation and 3.31% for Sember formation. These values were in agreement with the reported values in the literature.